Stretch Forming Studies on Thermoplastic Composite - Sivakumar, Dhar Malingam (2010)
Thermoplastic composites have the potential to revolutionise the automotive industry. They can reduce the weight of a car significantly, without compromising on structural rigidity. The use of thermoplastic composites is currently not widespread, due to the advantages metals have in ease of manufacture, being readily stamp formed. To date, many composite forming studies have centred around the draw forming of fabrics, with little consultation of the extensive body of knowledge on sheet metal forming. A different approach was taken by investigating the stretch forming behaviour of a pre-consolidated self-reinforced polypropylene composite (Curv®). This was accomplished by stamp forming blanks of varying geometry in a customised press that utilised a lock ring to enforce stretch forming conditions. Strains were measured throughout the forming process with an optical strain measurement system. The experimental results were used to generate a Forming Limit Diagram (FLD) for Curv at room temperature. It was determined that Curv® exhibits a considerably different forming behaviour to metals, and it was observed that there was a shift of the FLD into the positive minor strain region, suggesting that Curv can sustain larger minor strains for a given major strain than the metals used in comparison. Accordingly, Curv exhibits superior formability to Aluminium, facilitating the manufacture of more complex and intricate parts, within a comparative time frame.